Convergence and Coexistence Among The Schools Of Islamic Law: a Methodology - Muhammad Habibur Rahman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2016)
Most of the texts of Shari'ah came in the form of fundamentalprinciples and general provisions. The texts are often general and flexible at alarge extent, so that it would not be narrowed for the people. In addition, thetexts, which encompass the partial and detailed provisions of Shari'ah, are draftedin such a way that can accommodate more than single understanding andparticular interpretation. Consequently, this leads to the presence of multipleSchools and standpoints in the Islamic law. Nevertheless, all these Schools of Most of the texts of Shari'ah came in the form of fundamentalprinciples and general provisions. The texts are often general and flexible at alarge extent, so that it would not be narrowed for the people. In addition, thetexts, which encompass the partial and detailed provisions of Shari'ah, are draftedin such a way that can accommodate more than single understanding andparticular interpretation. Consequently, this leads to the presence of multipleSchools and standpoints in the Islamic law. Nevertheless, all these Schools of